STUDI AGAMA PERSPEKTIF INSIDER-OUTSIDER - Shokhibul Mighfar (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
Islam is no longer understood merely in terms of historical and doctrinal, but it has become a complex phenomenon. Desperately needed methodological skills to understand the religious data. In the last two decades, the growing awareness of the importance of various scientific approaches in the field of Islamic Studies and attention to the problems resulting from different approaches. We can distinguish, for example, approach to philology, historical, anthropological and sociological data on religion. In each approach can be found possibilities of certain methods are more critical and applicable than other methods. Similarly, the debate between insider (students of Islam from Islam itself) and outsider (incidentally orientalis) is also a separate section which is quite unique in Islamic studies. The phrase is quite interesting fact is the line between insider with outsider itself, experienced a shift, that no outsider should orientalis, but could be from the perspective of Islam itself which is different.